Yonder - Goossens, Marnix; van Bladel, Remco (Amsterdam : Roma Publications, 2013)
Dutch photographer Marnix Goossens spent seven years documenting surrogate nature in somewhat run-down interiors, a recurrent theme reflecting our underlying yearning for the freedom inspired by exotic destinations and wide-open spaces. In place of the real thing, Goossens pictures palm-print wallpaper, false wood grain adhesive, flowery motifs and faded posters of snow-capped mountains. Otherwise mundane and overlooked details and decorative elements are appreciated anew and in unexpected ways through a profusion of detail, colour nuances, and careful lighting. The book is published on the occasion of a solo exhibition by Goossens at Foam, Amsterdam. Exhibition: Foam, Amsterdam, The Netherlands (19.07.-06.10.2013).
Catalog of an exhibiton held at Foam, Amsterdam, July 18th 2013.
boek
Keywords: Goossens, Marnix